Strategi Pengembangan Sektor Unggulan dalam Pembangunan Ekonomi Berkelanjutan Kabupaten Lamongan - Imroatul Mutmainah; Hendry Cahyono (Universitas Negeri Surabaya, 2021)
The purpose of this research is to determine the leading sectors of Lamongan Regency byusing Location Quotient and Shift Share analysis. The data used in this research is theGross Regional Domestic Product (PDRB) of Lamongan and East Java Regency for 10years, 2010-2019. The method used is a mixed method, namely quantitative descriptiveand literature study. The results showed that the sector based on LQ> 1 is theagricultural sector; construction; transportation and communication; and the servicessector. Meanwhile, the non-base sector is the mining and quarrying sector; processingindustry; electricity, clean water and gas; real estate sector, corporate services sector;and the financial sector with LQ <1. The result of the shift share value in all sectors ofLamongan Regency with a positive value means that regional growth is experiencingrapid growth. The analysis of the sustainable development economic strategy uses aliterature study where Lamongan Regency has not yet reached sustainable development if it is only seen from the economic aspect and does not see all aspects in the sustainabledevelopment component. Different policy strategies are needed so that in each aspect inthe Lamongan Regency area in an effort to accelerate achievements towards thesustainable development of Lamongan Regency. Keywords: Economic Development, Leading Sectors, Sustainable Development,Lamongan Regency